Mindfulness meditation in nature - Manahan, Aisleen Mariz Arellano (Nanyang Technological University, 2022)
The present study looks into the concepts of Nature Therapy, Attention Restoration Theory, and Mindfulness which are each found to have restorative effects on an individual’s well-being. While most literature have established the restorative effects of nature exposure and mindfulness separately, little is still known about the effects of nature-based mindfulness. Hence, the purpose of this study is to investigate the restorative effects of mindfulness meditation in nature. More specifically, it was hypothesised that engaging in mindfulness meditation in an outdoor environment will lead to improved psychophysiological and cognitive outcomes as compared to doing so in an indoor environment. 60 participants were recruited and randomly assigned to an indoor or outdoor environment condition where they were tasked to complete a set of pre-meditation questionnaires and cognitive task, before engaging in a 10–30-minute mindfulness meditation, and then finally completing a set of post-meditation questionnaires and task. Participants in both indoor and outdoor conditions have demonstrated reduced perceived stress and negative affect, along with improved positive affect and cognitive performance. However, only participants in the outdoor condition experienced greater levels of relaxation after engaging in mindfulness meditation. Nevertheless, there were no significant differences in the effects of mindfulness meditation between both indoor and outdoor conditions across the other measures, indicating that engaging in mindfulness meditation indoors can yield similar restorative benefits as doing so outdoors. Present findings suggest that the effects of nature exposure and mindfulness may be influenced by: (1) the mindfulness practice used, and (2) the ongoing COVID-19 pandemic.